STUDY OF THE IMPACT OF FLOOD AND ITS MANAGEMENT ON PUBLIC INFRASTRUCTURE AND FACILITIES IN KOTO PARIK GADANG - Nazili Nazili (Ikatan Dosen Menulis, 2022)
Floods are a complex problem that often occurs in parts of Indonesia, especially in densely populated areas such as cities and villages. Batang Lolo District, South Solok Regency is one of the areas that is frequently flooded. Floods can cause significant losses, both in terms of material and human life, and can affect agricultural production in the area. Therefore, flood management is a serious concern. This study aims to calculate rainfall and flood discharge data for the next 25 years, as well as determine the impact caused by flooding based on information from the local community in Koto Parik Gadang Diateh District, Solok Selatan District. Based on the results of the calculation of rainfall and flood discharge, it was found that the maximum rainfall with a return period of 25 years in Batang Lolo, Koto Parik Gadang Diateh District, South Solok Regency, using the Normal Distribution, Gumbel, and Log-Pearson Type III methods are respectively 126.55 mm/hour, 6.902 mm/hour and 156.990 mm/hour. Meanwhile, the calculation of the flood discharge with a 25-year return period in Batang Lolo, Koto Parik Gadang Diateh District, Solok Selatan Regency, using the Melchoir and Hasper methods, yielded data of 1616.45 seconds/second and 445.85 seconds/second. This is expected to help in efforts to deal with flooding in the area.